Characteristics and the appearance of new whale sharks (Rhincodon typus) as a unique phenomenon in the Kwatisore waters within the Cenderawasih Bay National Park area, Papua - Yan Maruanaya; Alex Soleman Willem Retraubun; Samuel Frederik Tuhumury; James Abrahamsz (Tomini Journal of Aquatic Science, 2021)
Research on whale sharks (Rhincodon typus) was conducted from September 1st to December 20th, 2020 in Kwatisore waters. Kwatisore waters are within the conservation area of the Cenderawasih Bay National Park and have specifications for the number of whale sharks and the appearance of new individuals. The appearance of whale sharks individuals takes place every day around the boat life net area that is anchored in Kwatisore waters. This study aims to assess whale shark aggregation, particularly the total appearances and number of individual appearances in eight boat life net units. The number of appearances and the number of individual whale sharks is very dependent on the catch of anchovies by each boat life net unit and the feed of anchovies given by the fishermen. The results showed that there were 499 appearances of whale sharks consisting of 15 individuals, of which 13 individuals were identified, while 2 were new individuals who had not been identified. The new individual for ID 182 is named Yan Maruanaya and ID 183 is named Bram Maruanaya. The percentage of whale sharks appears during the period of September to December 2020 is 100% male with a length of 3 to 6 m.